Faktor-faktor yang Berhubung dengan Kejadian Bendungan Asi pada Ibu Nifas di Wilayah Puskesmas Darussalam Kabupaten Aceh Besar - Efni, Nur; Cut Yuniwati; Sastrinawati Sastrinawati (PT. Intelek Cendikiawan Nusantara, 2025)
Breast engorgement is a common lactation problem in postpartum mothers. This condition can lead to serious complications such as mastitis and breast abscesses. The WHO estimates that 20–40% of breastfeeding mothers worldwide experience breast engorgement in the first week postpartum. Contributing factors include suboptimal breast emptying, lack of knowledge, parity status, and breastfeeding that does not meet the baby's needs. Objective: To identify factors associated with breast engorgement in postpartum mothers in the Darussalam Community Health Center (Puskesmas) in Aceh Besar Regency. Methods: This study used an observational analytical design with a cross-sectional approach. The study population was 35 postpartum mothers, with 30 respondents selected through accidental sampling. The instrument was a questionnaire regarding breast emptying, knowledge, parity, and breastfeeding habits. Data were analyzed using the Chi-Square test with a significance level of 0.05. Results: There was a significant association between breast emptying (p = 0.002), knowledge (p = 0.010), parity (p = 0.007), and breastfeeding on demand (p = 0.001) with the incidence of breast engorgement. Conclusion: Breast emptying, knowledge, parity, and breastfeeding on demand were significantly associated with the incidence of breast engorgement. Education and support from healthcare providers are crucial for preventing breast engorgement early in the postpartum period.